2022
DOI: 10.1039/d2ra02820d
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric and naked-eye detection of arsenic(iii) using a paper-based microfluidic device decorated with silver nanoparticles

Abstract: Arsenic (As) as a metal ion has long-term toxicity and its presence in water poses a serious threat to the environment and human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 101 publications
2
18
0
Order By: Relevance
“…The lowering of the SPR observed may be due to the HCO 3 − induced adsorption of AsO 2 − ion on the surface of the NPs. From this study and some previous reports, 23–25 the proposed mechanism is shown in Scheme 1. The formation of silver ion–citrate complex formation followed by heat-induced chemical reduction and Ostwald ripening leads to the formation of Ag NPs, where citrate itself acts as capping agent to provide colloidal stability of Ag NPs.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The lowering of the SPR observed may be due to the HCO 3 − induced adsorption of AsO 2 − ion on the surface of the NPs. From this study and some previous reports, 23–25 the proposed mechanism is shown in Scheme 1. The formation of silver ion–citrate complex formation followed by heat-induced chemical reduction and Ostwald ripening leads to the formation of Ag NPs, where citrate itself acts as capping agent to provide colloidal stability of Ag NPs.…”
Section: Resultssupporting
confidence: 72%
“…The lowering of the SPR observed may be due to the HCO 3 − induced adsorption of AsO 2 − ion on the surface of the NPs. From this study and some previous reports, [23][24][25] the proposed mechanism is shown in Scheme 1.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…41–45 Based on these facts, AgNPrs have a special place in the construction of colorimetric sensors. 46 So far, several sensors and biosensors have been developed by either etching or the growth of different analytes onto this optical nanoprobe. 31,47…”
Section: Introductionmentioning
confidence: 99%